﻿Electrochemical mechanistic studies and electrochemical detection of caffeine and capsaicinoids extracted into an organic solvent - Chan, Kwok Kiong (2017)
Electrochemistry of food molecules have previously been studied in order to fundamentally understand their redox behaviour, and to see if this relates to their in vivo properties and to the metabolites that are formed. By employing electroanalytical techniques, the quantification of molecules in food samples could be achieved. Numerous electrochemical studies have been conducted in aqueous solution, focusing on the development of electrodes for quantitative purposes. However, very few studies were performed in organic solvents, which have similar environment to which non water soluble food molecules undergo metabolic reactions. Therefore, in this thesis, the electrochemistry of caffeine and capsaicinoids were explored in acetonitrile. The use of acetonitrile can reduce the chemical reaction between water in the solvent and the intermediate, allowing their redox behaviour, the intermediates and products all to be studied. In addition, detection methods for caffeine and capsaicinoids in acetonitrile were developed based on their electrochemical behaviour. Detection in acetonitrile allows for solid-phase extraction which aids in the removal of water-soluble interferences in samples. Moreover, the detection process is simple and easy with no electrode modification and could be performed in small volume, reducing reagents used.